The use of synchrotron X-ray scattering coupled with in situ mechanical testing for studying deformation and structural change in isotactic polypropylene - Davies, R. J.; Zafeiropoulos, N. E.; Schneider, K.; Roth, S. V.; Burghammer, M.; Riekel, C.; Kotek, J. C.; Stamm, M. (Colloid and polymer science, 2004)
The mechanical behaviour of semi-crystalline polymers is greatly influenced by the properties of the crystalline and the amorphous phases. As a result this topic has been the subject of extensive research. However, to date, a comprehensive relationship between the structure and mechanical properties for semi-crystalline polymers has yet to be established. This present study concerns the commissioning of a novel method for in situ data collection during the deformation of polymers. This involves the combination of three different techniques into a single experiment, namely tensile testing, synchrotron radiation wide angle X-ray scattering, and optical microscopy. For this current investigation, three isotactic polypropylene samples have been studied, produced using different thermal treatments. This enables the influence of thermal treatment on the mechanical properties and crystallographic structure to be assessed. The results indicate that tensile properties are influenced by thermal treatment via the relative fraction of β-phase material in the sample. As the temperature increases at which thermal treatment takes place, iPP ductility decreases due to the greater rigidity of the increasing α-phase content. Differences in crystal strain between the different iPP crystal phases are also observed although the reasons for such differences remain unclear.[PUBLICATION ABSTRACT]